Measurement of electrons from beauty-hadron decays in pp and Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; et al. (Physical review, 2023)
The production of electrons from beauty-hadron decays was measured at midrapidity in proton-proton (pp) and central Pb-Pb collisions at center-of-mass energy per nucleon-nucleon pair √sNN = 5.02 TeV, using the ALICE detector at the LHC. The cross section measured in pp collisions in the transverse momentum interval 2<pT<8GeV/c was compared with models based on perturbative quantum chromodynamics calculations. The yield in the 10% most central Pb-Pb collisions, measured in the interval 2<pT<26GeV/c, was used to compute the nuclear modification factor RAA, extrapolating the pp reference cross section to pT larger than 8 GeV/c. The measured RAA shows significant suppression of the yield of electrons from beauty-hadron decays at high pT and does not show a significant dependence above 8GeV/c within uncertainties. The results are described by several theoretical models based on different implementations of the interaction of heavy quarks with a quark-gluon plasma, which predict a smaller energy loss for beauty quarks compared to light and charm quarks.
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovska, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, J. Kim, M. Kim, M. Kroesen, J.A. Lopez, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. Van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und 1005 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Gesehen am 21.05.2024